2020
DOI: 10.1007/s11442-020-1722-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring global food security pattern from the perspective of spatio-temporal evolution

Abstract: Food security is the primary prerequisite for achieving other Millennium Development Goals (MDGs). Given that the MDG of "halving the proportion of hungers by 2015" was not realized as scheduled, it will be more pressing and challenging to reach the goal of zero hunger by 2030. So there is high urgency to find the pattern and mechanism of global food security from the perspective of spatio-temporal evolution. In this paper, based on the analysis of database by using a multi-index evaluation method and radar ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…In fact, the COVID-19 pandemic has further exacerbated world hunger (Laborde et al 2020 ; Zurayk 2020 ). Thus, food security will remain a global priority for decades to come (Conceição et al 2016 ; Sisha 2020 ) and a prerequisite for other Millennium Development Goals (Cai et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the COVID-19 pandemic has further exacerbated world hunger (Laborde et al 2020 ; Zurayk 2020 ). Thus, food security will remain a global priority for decades to come (Conceição et al 2016 ; Sisha 2020 ) and a prerequisite for other Millennium Development Goals (Cai et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although food security is in a race against population growth, Grote (2014) and Goyal (2012) showed that population pressure, poverty, land degradation, and unstable environments had pushed food security further out of reach. This has been compounded by climate change and natural disasters (Cai et al, 2020). Douglas (2009) stated that agricultural development, people's purchase ability, regional accessibility, and social, psychological, behavioral, political, and economic stability are factors affecting food security.…”
Section: Food Security In Indonesia 41 An Overviewmentioning
confidence: 99%
“…Further, it is found that decrease in cereal production not only increases the prices of cereal goods but also effect the consumption of individual households which is expected to decrease in all four countries (see Figure 7 ). This can be seen as that these South Asian countries can face more problems of food security, as they are already lagging in average yields and facing already a largely undernourished population ( Bandara and Cai, 2014 ; Cai et al., 2020 ). Further the loss of welfare is identified due to the climate change which is 49.224 billion US $ in India, 32.161 billion in Pakistan, 28.198 billion in Bangladesh, and 5.661 billion in Sri-Lanka (see Figure 8 ).…”
Section: Economic Impacts Of Climate Changementioning
confidence: 99%
“…In IAM, climate was first integrated into the macro-economic model by representation of carbon dioxide concentrations in the classical model of the long-run growth ( Nordhaus 1975 , 1977 , 1992 ). This model consists of combined data on the growth of crops, usage of soil and some other economic models ( Mendelsohn et al., 2016 ; Prinn et al., 1999 ; Fujino et al., 2006 ; Cai et al., 2020 ; Müller et al., 2020 ; Meijl et al., 2020 ). The IAM developed a single entity by using the cause and effect of change in climate and by collecting the knowledge from different disciplines into a single entity and ultimately developing a network of information for developing policies ( Dinar and Mendelsohn, 2011 ; Vanschoenwinkel et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%